Redox polymers incorporating pendant 6‐oxoverdazyl and nitronyl nitroxide radicals. Issue 2 (8th January 2020) - Anghel, Michael; Magnan, François; Catingan, Sara D.; McCready, Matthew A.; Aawani, Elaheh; Wong, Victor; Singh, Deepa; Fanchini, Giovanni; Gilroy, Joe B.
ABSTRACT: Polymers comprised of redox‐active organic radicals have emerged as promising materials for use in a variety of organic electronics, including fast‐charging batteries. Despite these advances, relatively little attention has been focused on the diversification of the families of radicals that are commonly incorporated into polymer frameworks, with most radical polymers being comprised of nitroxide radicals. Here, we report two new examples prepared via ring‐opening methathesis polymerization containing 6‐oxoverdazyl and nitronyl nitroxide radicals appended to their backbones. The polymerization reaction and optoelectronic properties were explored in detail, revealing high radical content and redox activity that may be advantageous for their use as semiconducting thin films. Initial studies revealed that current–voltage curves obtained from thin films of the title polymers exhibited memory effects making them excellent candidates for use in resistive memory applications. © 2020 Wiley Periodicals, Inc. J. Polym. Sci. 2020, 58, 309–319 Abstract : Polymers containing pendant 6‐oxoverdazyl or nitronyl nitroxide radicals have been prepared by ring‐opening metathesis polymerization. Their film‐forming and redox properties render them excellent candidates for resistive memory applications.